(untitled) (Aptisi Transactions on Technopreneurship (ATT), 2023)
This study investigates the impact of hedonic and utilitarian values on customer satisfaction and behavioral intentions in the Muslim clothing market, focusing on CV. Rabbani Asysa Ponorogo’s products. Employing a quantitative approach, the research uses questionnaires analyzed with SEM-PLS 4.0 and involves a purposive sample of 100 respondents. This study is significant for its specific examination of the Muslim fashion industry, addressing a gap in understanding consumer behavior in this niche market. The findings reveal that while hedonic values significantly influence both customer satisfaction and behavioral intentions, utilitarian values only impact customer satisfaction, not behavioral intentions. Customer satisfaction is also a significant determinant of behavioral intentions. The research concludes that balancing both hedonic and utilitarian aspects is crucial for enhancing customer satisfaction and behavioral intentions in this sector.